2010
DOI: 10.1080/10426500902994320
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Multibenzo Oxygen–Sulfur Donor Macrocycles Containing Lactams at Room Temperature

Abstract: Some new oxygen-sulfur, multibenzo macrocyclic ligands containing amide groups have been prepared using the macrocyclization process with the reaction of 2,2 -thiobis-[4-methyl(2-aminophenoxy)phenyl ether] as a symmetrical diamine with appropriate dicarboxylicacid dichlorides in moderate yields. This macrocyclization led to the formation of diand tetramide macrocycles. These reactions were routinely carried out at ambient temperature in CH 2 Cl 2 as solvent in high dilution without template effect conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These reactions were routinely carried out at ambient temperature in CH 2 Cl 2 as solvent in high dilution without template effect conditions. It is found that sulfur atom affects the rigidity of the macrocycles and diastereotopicity of nuclei in the ring of these series of macrocyclic compounds [69].…”
Section: Mixed Macrocyclesmentioning
confidence: 96%
“…These reactions were routinely carried out at ambient temperature in CH 2 Cl 2 as solvent in high dilution without template effect conditions. It is found that sulfur atom affects the rigidity of the macrocycles and diastereotopicity of nuclei in the ring of these series of macrocyclic compounds [69].…”
Section: Mixed Macrocyclesmentioning
confidence: 96%
“…In our previous work, we have described the synthesis of new bis-Betti bases [10] and new multibenzo oxygen-sulfur donor macrocycles containing lactams [11] from dibenzosulfide (2) and diamine (3), respectively. In the present study, we report the synthesis of a new bisamine containig a dibenzosulfide moiety.…”
Section: Introductionmentioning
confidence: 99%